2008
DOI: 10.1179/147683008x301513
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of L-theanine and caffeine on cognitive performance and mood

Abstract: The aim of this study was to compare 50 mg caffeine, with and without 100 mg L-theanine, on cognition and mood in healthy volunteers. The effects of these treatments on word recognition, rapid visual information processing, critical flicker fusion threshold, attention switching and mood were compared to placebo in 27 participants. Performance was measured at baseline and again 60 min and 90 min after each treatment (separated by a 7-day washout). Caffeine improved subjective alertness at 60 min and accuracy on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 19 publications
6
88
2
Order By: Relevance
“…Such results are in line with previous research showing that tea containing caffeine (40-90 mg) and theanine (36-97 mg) enhanced alertness and reduced calmness relative to a placebo tea (De Bruin et al 2011;Giesbrecht et al 2010). Similarly, studies that differentiated between the influence of caffeine (50-150 mg) and theanine (100-250 mg) found that, when consumed together, caffeine and theanine enhanced alertness and reduced fatigue (Haskell et al 2008;Owen et al 2008). However, we found no evidence that theanine ameliorated the effects of caffeine on other mood dimensions, including tension, anger, and confusion.…”
Section: Subjective and Physiological Mood And Arousalsupporting
confidence: 80%
See 3 more Smart Citations
“…Such results are in line with previous research showing that tea containing caffeine (40-90 mg) and theanine (36-97 mg) enhanced alertness and reduced calmness relative to a placebo tea (De Bruin et al 2011;Giesbrecht et al 2010). Similarly, studies that differentiated between the influence of caffeine (50-150 mg) and theanine (100-250 mg) found that, when consumed together, caffeine and theanine enhanced alertness and reduced fatigue (Haskell et al 2008;Owen et al 2008). However, we found no evidence that theanine ameliorated the effects of caffeine on other mood dimensions, including tension, anger, and confusion.…”
Section: Subjective and Physiological Mood And Arousalsupporting
confidence: 80%
“…This research has demonstrated that caffeine reliably enhances vigilance and psychomotor performance (Smith 2011) and may enhance processes that require executive control, including response inhibition (Barry et al 2007), selective visual attention (Brunyé et al 2010a(Brunyé et al , 2010b, and working memory (Addicott and Laurienti 2009). Caffeine and theanine, consumed together, exert similar effects to that of caffeine alone, in that 35-50 mg caffeine and 90-100 mg theanine enhanced mental alertness, task-switching attention, and recognition memory relative to placebo (Einöther et al 2010;Giesbrecht et al 2010;Kelly et al 2008;Owen et al 2008). Opposite doses, i.e., 90-100 mg caffeine and 36-46 mg theanine exerted similar effects (De Bruin et al 2011).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Theanine is readily bioavailable from both green and black tea, crosses the blood-brain barrier, and has demonstrated effects on brain function. 41 The chemical structure of theanine, which contains the glutamate molecule, suggests that it might reduce glutamate-related endothelial damage. Studies of middle cerebral artery occlusion in mice have demonstrated a neuroprotective effect of ␥-glutamylethylamide (theanine) and at dosages of 05 and 1.0 mg/kg, it reduces the size of the cerebral infarct in the gerbil.…”
Section: Arab Et Al Green and Black Tea Consumption And Risk Of Strokementioning
confidence: 99%